Counteracting Hoax In Social Media Network Approach Through Tarbiyah Dzatiyah - Muhamad Tisna Nugraha (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: The more rapid technological progress is marked by the cheapness and easier of people to connect in social media. This thing makes the number of users increasing significantly every year. In addition, a variety of social media features come on the market also encourage users to share every activities, knowledge, opinions, writings, even reconnect their relationship with old friends who are separate without limits of time and place. But the existence of social media doesn’t always have a positive effect, some individuals or even groups use this service as a means of spreading a false news or known as Hoax. The spread of this news is a strartegi to drop others, causing panic, and gave rise to debate. The genesis of misunderstanding as a result of the spread hoax was able to invite hostility which is if left unchecked and arounding on a large scale could lead to World War that lead to mass killings, poverty and hunger. Tarbiyah dzatiyah as a self-learning approach to create a perfect Islamic personality throughout his side start from scientific, faith, morals, social and other. Is one solution that can be offered to prevent hoax news in social media, because tarbiyah dzatiyah teach every individual to start everything from the smallest, from ourselves, and from now on. Keywords: Hoax, Social Media, Tarbiyah Dzatiyah